Assessment of Average Tracer Concentration Approach for Flow Rate Measurement and Field Calibration - P. Sidauruk; S Satrio; E.R. Pujiindiyati (PPIKSN-BATAN, 2015)
Tracer method is one of the methods available for open channel flow rate measurements such as in irrigation canals. Average tracer concentration approach is an instantaneous injection method that based on the average tracer concentrations value at the sampling point. If the procedures are correct and scientific considerations are justified, tracer method will give relatively high accuracy of measurements. The accuracy of the average tracer concentration approach has been assessed both in laboratory and field. The results of accuracy tests of open channel flow that has been conducted at the Center for Application Isotopes and Radiation Laboratory-BATAN showed that the accuracy level of average concentrations approach method was higher than 90% compared to the true value (volumetric flow rate). The accuracy of average tracer concentration approach was also assessed during the application of the method to measure flow rate of Mrican irrigation canals as an effort to perform field calibration of existing weirs. Both average tracer concentration approach and weirs can predict the trend of the flow correctly. However, it was observed that flow discrepancies between weirs measurement and average tracer concentration approach predictions were as high as 27%. The discrepancies might be due to the downgrading performances of the weirs because of previous floods and high sediment contents of the flow.Received: 03 June 2015; Revised: 06 July 2015; Accepted: 08 July 2015